An Effort to Increase Organ Donor Registration Through Intergroup Competition and Electronic Word of Mouth. Issue 3 (3rd March 2016) - Smith, Sandi W.; Hitt, Rose; Park, Hee Sun; Walther, Joseph; Liang, Yuhua (Jake); Hsieh, Gary
Abstract : The effort to increase Web organ donation registrations in Michigan by enhancing 2 types of university campaigns with social media strategies informed by social identity theory is the focus of this research. The two campaigns focused on either ingroup or rivalry outgroup social identification, and each was enhanced with individually focused social media in the first year of the campaign and with electronic word of mouth in Year 2 of the campaign. Results indicated that individually focused social media such as Facebook ads worked well in rivalry campaigns (in which registrations increased two times over baseline) but not in ingroup identification campaigns (in which registrations decreased significantly over baseline when ads were introduced in the first year of each type of campaign). Electronic word-of-mouth strategies worked well in both ingroup identification campaigns (in which registrations increased two times over baseline) and rivalry campaigns (in which registrations rose almost eight times over baseline, when strategies were introduced in the second year of each type of campaign).